Strategi Inovatif Metode Bermain Peran dalam Pendidikan Agama Islam untuk Meningkatkan Antusias dan Pemahaman Peserta Didik - Handayani, Fitri; Syafii, Imam; Fahmi, Muhammad; Iman, Aldi Khusmufa Nur (PAKAR Pendidikan, 2025)
Islamic Religious Education (IRE) plays a crucial role in shaping students' character and moral values from an early age. However, instructional approaches in IRE remain dominated mainly by lecture-based methods, which tend to result in passive learning and decreased student engagement. This issue is particularly evident in Integrated Islamic Elementary Schools, where conventional teaching strategies often fail to stimulate students' interest, ultimately leading to low learning outcomes. To address this challenge, there is a need for innovative and participatory learning strategies, such as the role-playing method. This study aims to analyze the effectiveness of implementing role-playing as an instructional strategy to enhance student engagement and conceptual understanding in Islamic Religious Education. A qualitative case study approach was employed at SDIT Al-Halimiyah, Jakarta. Data were collected through classroom observations, in-depth interviews, and document analysis. The data analysis involved three main stages: data condensation, data display, and conclusion drawing. The findings reveal that role-playing significantly increases active student participation, strengthens their understanding and retention of religious concepts, and fosters the development of confidence, empathy, and social awareness. Furthermore, students demonstrated higher enthusiasm and comprehension when learning was delivered through experiential and interactive methods. These results suggest that role-playing can be an effective alternative instructional strategy in Islamic Religious Education, promoting active learning and contributing to the overall quality of religious education at the elementary school level.